Oxidation of hydrochar produced from byproducts of the sugarcane industry for the production of humic-like substances: Characterization and interaction study with Cu(II) - Moura, Bernardo R. [UNESP]; Santos, Vinicius S. [UNESP]; Metzker, Gustavo [UNESP]; Ferreira, Odair P.; Bisinoti, Márcia C. [UNESP]; Boscolo, Mauricio [UNESP]; Moreira, Altair B. [UNESP] (Elsevier, 2023)
Humic-like substances (HLS) are molecules extracted in an alkaline medium from different materials that have not been subjected to the natural process of humification that occurs in the soil. HLS have the potential to be used as organic fertilizers due to their ability to incorporate micronutrients such as Cu(II) and Co(II); in addition, they represent an alternative for the remediation of contaminated areas due to their high affinity for metals. HLS can be extracted from hydrochar (HC) but only with low yields of approximately 5%. Therefore, the present study aimed to increase the amount of HLS extracted from the HC produced from byproducts of the sugarcane industry through the oxidation of HC with HNO3. HLS extracted from oxidized and unoxidized HC were characterized by CHNS analysis and 13C CPMAS NMR. The interaction between HLS and Cu(II) was studied by molecular fluorescence quenching (EEM-PARAFAC) and applying the Ryan and Weber complexation model. The oxidation of HC with HNO3 allowed high yields of extracted HLS of above 80%. The oxidation carried out with 30% HNO3 for 2 h showed the best result, since the HLS30%(2h) were extracted with a very high yield (88.3%) in a short period of time. Oxidation promoted a decrease in HLS aromaticity and an increase in oxygen and nitrogen groups. HLS showed high affinity for Cu(II), as evidenced by the high logK values (between 5.5 and 5.9). HLS extracted from oxidized HCs showed higher complexation capacity due to the greater incorporation of the oxygenated groups promoted by oxidation, which are fundamental during the interaction with metallic cations. Therefore, the oxidation of HC substantially increased the production of HLS, representing a big advance for the production of carbonaceous materials with higher added value from byproducts of the sugarcane industry produced on a large scale in Brazil.
Keywords: Complexation; Humic-like substances; Hydrochar; Oxidation; PARAFAC